Negative pressure wound therapy aids recovery following surgical debridement due to severe bacterial cellulitis with abdominal abscess post-cesarean: A case report (CARE-Compliant). Issue 50 (December 2016) - Young, Christopher N.J.; Ng, Ka Ying Bonnie; Webb, Vanessa; Vidow, Sarah; Parasuraman, Rajeswari; Umranikar, Sameer
Abstract: Introduction: Bacterial cellulitis post-Cesarean section is rare. Negative pressure wound therapy (NPWT) is widely used in various medical specialities; its effectiveness in obstetrics however remains the topic of debate—used predominantly as an adjunct to secondary intention specific to high-risk patient groups. Its application in the treatment of actively infected wounds post-Cesarean is not well documented. Here, we document NPWT in the treatment of an unusually severe case of bacterial cellulitis with abdominal abscess postpartum. We provide a unique photographic timeline of wound progression following major surgical debridement, documenting the effectiveness of 2 different NPWT systems (RENASYS GO and PICO, Smith & Nephew). We report problems encountered using these NPWT systems and "ad-hoc" solutions to improve efficacy and patient experience. A 34-year-old primiparous Caucasian female with no prior history or risk factors for infection and a normal body mass index (BMI) presented with severe abdominal pain, swelling, and extensive abdominal redness 7 days postemergency Cesarean section. Examination revealed extensive cellulitis with associated abdominal abscess. Staphylococcus aureus was identified in wound exudates and extensive surgical debridement undertaken day 11 postnatally due to continued febrile episodes and clinical deterioration, despite aggressive intravenous antibiotic therapy. Occlusive NPWT dressings were applied for a period of 3 weeks before discharge, as well as a further 5 weeks postdischarge into the community. NPWT was well tolerated and efficacious in infection clearance and wound healing during bacterial cellulitis. Wound healing averaged 1 cm 2 per week before NPWT withdrawal; cessation of NPWT before full wound closure resulted in significantly reduced healing rate, increased purulent discharges, and skin irritation, highlighting the efficacy of NPWT. Five-month follow-up in the clinic found the wound to be fully healed with no additional scarring beyond the boundaries of the original Cesarean incision. The patient was pleased with treatment outcomes, reporting no lasting pain or discomfort from the scar. Conclusions: This report represents the first documented use of NPWT to aid healing of an actively infected, open wound following extensive surgical debridement 10 days post-Cesarean section, confirming both the efficacy and tolerability of NPWT for the treatment of severe bacterial cellulitis in obstetric debridement.